The correlation of metabolic and renal biomarkers with vitamin D status in postmenopausal women - Klisic, Aleksandra (Journal of Medical Biochemistry, 2023)
Objective: To our knowledge, the mutual involvement of a variety of metabolic and renal biomarkers and vitamin D (determined as 25-hydroxyvitamin D [25(OH)D]) in postmenopausal women has not been examined yet. Therefore, we aimed to explore such a relationship by a thorough statistical multimarker approach. Patients and Methods: A total of 150 (diabetes and cardiovascular disease-free) postmenopausal women were included. Anthropometric and biochemical parameters were measured. The fatty liver index (FLI) and Homeostasis model assessment of insulin resistance (HOMA-IR) were calculated. Univariate and multivariate binary logistic regression analyses were used to test the predictions of cardiometabolic markers for [25(OH)D] status. Principal component analysis (PCA) was applied to explore the effect of examined biomarkers on [25(OH)D] status. Results: Univariate binary regression analysis revealed positive associations between FLI and [25(OH)D] [OR=1.036 (1.020-1.052), P<0.001] and HOMA-IR with [25(OH)D] [OR=2.385 (1.601-3.551), P<0.001]. Multivariate logistic regression analysis with backward selection enabled us to find the best model consisting of two markers, i.e. FLI [OR=1.032 (1.016-1.048), P<0.001] and glucose [OR=2.167 (1.001-4.693), P=0.050] associated with the first tertile of [25(OH)D]. PCA extracted 2 significant factors: Renal function-related factor and Metabolic syndrome-related factor. Renal function-related factor [i.e. creatinine, uric acid, retinol-binding protein 4 (RBP4) and cystatin C] explained 29% of the variance. Also, Metabolic syndrome-related factor (i.e. HOMA-IR, FLI, hsCRP and fibrinogen) explained 29% of the variance of the tested parameters. Moreover, binary logistic regression analysis revealed significant positive predictive ability of both factors, i.e. Renal function-related factor and Metabolic syndrome-related factor (P=0.044 and P<0.001, respectively) towards [25(OH)D] status. Conclusion: The joint involvement of renal function biomarkers and metabolic syndrome-related features (i.e. insulin resistance, inflammation and non-alcoholic fatty liver disease) can differentiate postmenopausal women with lower [25(OH)D] levels from other women.